2017
DOI: 10.3390/rs9121271
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Smoothing Methods for Reconstructing NDVI Time-Series and Estimating Vegetation Phenology from MODIS Data

Abstract: Many time-series smoothing methods can be used for reducing noise and extracting plant phenological parameters from remotely-sensed data, but there is still no conclusive evidence in favor of one method over others. Here we use moderate-resolution imaging spectroradiometer (MODIS) derived normalized difference vegetation index (NDVI) to investigate five smoothing methods: Savitzky-Golay fitting (SG), locally weighted regression scatterplot smoothing (LO), spline smoothing (SP), asymmetric Gaussian function fit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
118
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(125 citation statements)
references
References 73 publications
4
118
0
3
Order By: Relevance
“…Additionally, for each NDVI 16-day composite raster, the raster that represents the day of others. However, spline smoothing provides rather good results and its parameters can be well tuned through cross-validation [45]. Therefore, temporal gap filling is done using NDVI and NDVI_DOY information pixel-wise, by fitting a cubic smoothing spline.…”
Section: Filling Spatial and Temporal Data Gapsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, for each NDVI 16-day composite raster, the raster that represents the day of others. However, spline smoothing provides rather good results and its parameters can be well tuned through cross-validation [45]. Therefore, temporal gap filling is done using NDVI and NDVI_DOY information pixel-wise, by fitting a cubic smoothing spline.…”
Section: Filling Spatial and Temporal Data Gapsmentioning
confidence: 99%
“…Even with both satellites used synergically, the NDVI observations are ideally available every 9 days, which is too sparse for modeling daily SSM. The smoothing methods provide relatively simple, yet effective way for reconstructing NDVI time-series [45]. No smoothing method can be recommended more than others.…”
Section: Correlation Between Daily Filled Predictors and In Situ Soilmentioning
confidence: 99%
“…In Mianab region of Iran sugarcane yield was estimated via time series evaluation of NDVI, GNDVI and EVI vegetation indices and the results showed that NDVI and GNDVI vegetation indices with R 2 =0.63, RMSE=4.71 ton/ha and R 2 =0.60, RMSE 4.93 ton/ha, respectively, have good relations with sugarcane stem yield efficiency in regional scale (Khosravirad, Omid, Sarmadian, & Hosseinpour, 2019). Many time-series smoothing methods can be used for reducing noise and extracting plant phonological parameters from remotely-sensed data, but there is still no conclusive evidence in favour of one method over the others (Cai, Jönsson, Jin, & Eklundh, 2017). There is a clear interest for managers and decision-makers to have tools capable of monitoring continuously the vegetative vigour of sugarcane and providing timely information regarding potential short-term impacts of weather conditions on yield expectations.…”
Section: Introductionmentioning
confidence: 99%
“…One common methodology to derive the timing of crop calendar events is based on thresholds of the remote signal being previously filtered or smoothed, although this performance is site-specific, and strongly affected by the suitability of the specified threshold [5,6]. Alternatively, more robust methods are based on fitting a local mathematical model to the curve described by the signal.…”
Section: Introductionmentioning
confidence: 99%
“…Detailed data of seasonal vegetation changes over large areas can only be objectively and cost-effectively obtained by using the time-series of satellite images with high temporal resolution. Investigations of this issue have been commonly based on the analysis of diverse data sources and the assumption that cropping areas follow an annual cycle (growth, maturity, and senescence) that can be represented by the change of the remote signal (e.g., seasonal Normalized Difference Vegetation Index (NDVI) values) throughout the time [1-4].One common methodology to derive the timing of crop calendar events is based on thresholds of the remote signal being previously filtered or smoothed, although this performance is site-specific, and strongly affected by the suitability of the specified threshold [5,6]. Alternatively, more robust methods are based on fitting a local mathematical model to the curve described by the signal.…”
mentioning
confidence: 99%